STRATEGY TO ENHANCE THE COMPETENCIES OF CIVIL SERVANTS AT THE REGIONAL REVENUE AGENCY OFFICE OF BEKASI CITY - Handayani*, Kuntari; Rivai, Firman Hadi; Asropi, Asropi (Jurnal Apresiasi Ekonomi, 2024)
The Regional Revenue Agency of Bekasi City, a government body providing public services, exhibits a competency gap between the civil servants' (ASN) current skills and those required by the organization. This study aims to identify the factors causing this gap and develop strategies to enhance ASN competencies at the agency. Employing a qualitative descriptive approach, the research utilized interviews, observations, and literature review. The analysis, based on theories by Zwell and West, identified Belief, Skills, Experience, Personality Characteristics, Motivation, Emotional Issues, Intellectual Abilities, and Creativity as key competency factors. The findings indicate that the primary gaps are in Skills, Employee Characteristics, and Intellectual Abilities. In contrast, Belief, Experience, Motivation, Emotional Issues, and Creativity are strengths supporting competency improvement. Based on these insights, the study proposes a competency enhancement strategy for the Bekasi City Regional Revenue Office. This includes redesigning job competency standards, conducting competency assessments, allocating budget for competency development, implementing educational and training programs, and evaluating the effectiveness of these initiatives in improving competencies. Keywords: Competence, Human Resources, Strategy